2008
DOI: 10.1152/ajpgi.90434.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide activates NF-κB by TLR4-Bcl10-dependent and independent pathways in colonic epithelial cells

Abstract: Bhattacharyya S, Dudeja PK, Tobacman JK. Lipopolysaccharide activates NF-B by TLR4-Bcl10-dependent and independent pathways in colonic epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
2
36
1
Order By: Relevance
“…In both human colonic epithelial cells with a silenced BCL10 gene and the intestinal tissue of Bcl10 -/-mice, it has been shown that the TLR4 response is BCL10 dependent. However, other studies have shown that TLR4 signaling may follow both BCL10-dependent and -independent pathways (22)(23)(24)(25)(26). Although we did not test epithelial cells from P1, the results we obtained for fibroblasts were consistent with those of previous studies on epithelial cells (36), which indicates that the TLR4 response is BCL10 dependent and IKKB dependent in human fibroblasts.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In both human colonic epithelial cells with a silenced BCL10 gene and the intestinal tissue of Bcl10 -/-mice, it has been shown that the TLR4 response is BCL10 dependent. However, other studies have shown that TLR4 signaling may follow both BCL10-dependent and -independent pathways (22)(23)(24)(25)(26). Although we did not test epithelial cells from P1, the results we obtained for fibroblasts were consistent with those of previous studies on epithelial cells (36), which indicates that the TLR4 response is BCL10 dependent and IKKB dependent in human fibroblasts.…”
Section: Resultssupporting
confidence: 88%
“…In fibroblasts, a heterotrimer consisting of CARD10 (also known as CARMA3), BCL10, and MALT1 forms. Many studies have on epithelial cells (such as human colonic epithelial cells) in which BCL10 was silenced, and in intestinal cells from Bcl10 -/-mice, have demonstrated that the TLR4 response is BCL10 dependent (22)(23)(24)(25)(26). We therefore analyzed the effect of BCL10 deficiency in primary fibroblasts from P1, which we compared with cells from healthy donors, by measuring the production of IL-6 and IL-8 in response to TLR4, TLR2/6, Dectin-1, and TLR3 stimulation ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…In this report, we extend findings from our previous studies about how activation of canonical and noncanonical signaling of NF-B is mediated by BCL10 following stimulation by carrageenan (CGN) or lipopolysaccharide in human colonic epithelial cells (2)(3)(4)(5)(6)10). The sulfated polysaccharide CGN has been used for decades to induce inflammation in animal models to study mediators of inflammation and pharmacological agents that reduce inflammation.…”
supporting
confidence: 77%
“…53 Absence of TLR-4 in HBEC challenged with media, LPS, IL-13, and supernatant from control or LPStreated MDM suggests that HBEC may have responded to LPS via a TLR-4-independent pathway like other epithelial cells do. 54 Moreover, a basolateral HBEC response to LPS could be a relevant defensive mechanism towards infiltrating pathogens, increasing airway mucus to prevent additional microbial invasion. HBEC stimulated with supernatant from control MDM result in a partial inhibition of MUC5B, and none of the cytokines tested could reproduce this effect.…”
Section: Discussionmentioning
confidence: 99%